CHATBOT SERVICES AT EDUCATIONAL INSTITUTIONS WITH CUSTOMER RELATIONSHIP MANAGEMENT - Bambang Moertono Setiawan; Zulhawati Zulhawati; Agra Laksmi Maitri; Joko Sutopo (AIBPM Publisher, 2019)
Online services at Educational Institutions are currently an essential means of interacting with customers both for promotion, academic services or various information on agency activities. The problem that occurs is limited service time that cannot be continuously online, outside working hours and customers who do not have time, to come to the institution to get various information. This study seeks to develop a solution to create a service interaction system that can provide answers automatically online, known as chatbot. The method developed in this chatbot uses text-based data mining that combines database work processes using Customer Relationship Management (CRM). The results of this study found that the relationship between customer interactions, institutions and chatbot applications were reviewed with CRM in the information service satisfaction level of 82% of the use of chatbot. Chatbot can help meet customer and institutional information needs.